FACTORS CONTRIBUTING PRE-SERVICE ENGLISH TEACHER SPEAKING ANXIETY - Wilda Fuadiyah; Indah Nur Yunita; Maman Suryaman (PROJECT (Professional Journal of English Education), 2022)
This study focuses on the factors of speaking anxiety experienced by pre-service English teachers. In this study, the researcher uses a qualititative research with embracing a case study design. The data was collected from Foreign Language Classroom Anxiety Scale questionnaire developed by Horwitz et al. (1986) through Google Form provided to 22 English language education students. It has 33 items on a 5-point Likert scale. Using Oetting scale, the data that has been collected will be categorized and then interpreted. Based on the results of the questionnaire, the positive statement showed that some pre-service English teachers were still undecided in their speaking skills, and in the negative statement almost they agreed that they were anxious in English speaking. Keywords:  Anxiety, Pre-Service English Teachers, Speaking